Alkaloid contents in members of Lycopodiales - Tamayo Castillo, Giselle (2001)
The composition of alkaloids in fifteen species that belong to the Lycopodiales, which grow wild in Costa Rica were analysed by gas chromatography coupled with mass spectrometry. Several alkaloids were identified, including dihydrolycopodine, muscopyridine, lycocernuine, lofoline, lycodoline and lycopodine.